Analisis Curahan Jam Kerja Perempuan di Kabupaten Jember: An Analysis of Women's Working Hours Allocation in Jember Regency - H. Mohammad Saleh (Fenomena, 2004)
The growing participation of women in Indonesia's labor force, particularly in Jember Regency, significantly contributes to family economies despite limited job opportunities. Drawing on Becker's time allocation theory, this study analyzes the working hours and employment status (full-time or part-time) of female day and night workers. Primary data were collected from 250 female respondents aged 25–49 years working in agriculture, industry, trade, and services, using cluster sampling and cross-tabulation analysis. The results show that average weekly working hours are similar between day workers (47.69 hours) and night workers (47.31 hours). Furthermore, 93.57% of day workers and 93.67% of night workers are classified as full-time workers (≥35 hours/week). The study concludes that women's labor participation is high and contributes to economic development; however, improvements in business management and government policy support—especially for women with limited capital—are necessary to enhance family welfare and the regional economy. Fenomena meningkatnya partisipasi wanita dalam angkatan kerja di Indonesia, khususnya di Kabupaten Jember, menunjukkan adanya kontribusi signifikan terhadap perekonomian keluarga meskipun menghadapi keterbatasan lapangan kerja. Berdasarkan teori alokasi waktu Becker, penelitian ini bertujuan untuk menganalisis curahan jam kerja pekerja wanita siang dan malam serta status jam kerja mereka (penuh atau tidak penuh). Penelitian menggunakan data primer dari 250 responden wanita usia 25–49 tahun yang bekerja di sektor pertanian, industri, perdagangan, dan jasa, dengan metode cluster sampling dan analisis tabulasi silang. Hasil penelitian menunjukkan rata-rata jam kerja per minggu relatif sama antara pekerja siang (47,69 jam) dan malam (47,31 jam). Sebanyak 93,57% pekerja siang dan 93,67% pekerja malam tergolong pekerja penuh (≥35 jam/minggu). Kesimpulannya, partisipasi wanita dalam dunia kerja cukup tinggi dan berkontribusi terhadap pembangunan ekonomi, namun perlu peningkatan manajemen usaha dan dukungan kebijakan pemerintah, terutama bagi wanita bermodal kecil, untuk meningkatkan kesejahteraan keluarga dan perekonomian daerah.